Bioequivalence Studies of a Reformulated Dutasteride and Tamsulosin Hydrochloride Combination Capsule and a Commercially Available Formulation. Issue 5 (27th January 2017) - Kurczewski, Renee; Bowen, Chet; Collins, David; Zhu, John; Serbest, Gulyeter; Manyak, Michael
Abstract: A dutasteride 0.5 mg and tamsulosin hydrochloride 0.4 mg combination (DTC) capsule (Duodart ® ) was reformulated to reduce the capsule size and enhance product stability. Bioequivalence of the reformulated DTC capsule with the commercial formulation was evaluated in 2 single‐dose, open‐label, randomized, 2‐way crossover studies in healthy adult male volunteers. Subjects in a fasted or fed state received a single oral dose of either the reformulated DTC or the commercial formulation followed by a 28‐day washout period between treatments. Blood samples were taken predose and up to 72 hours postdose for pharmacokinetic (PK) analysis of dutasteride and tamsulosin serum concentrations. From the serum concentration‐vs‐time data, a noncompartmental method was used to calculate the maximum observed serum concentration (Cmax ) and area under the serum concentration‐time curve (AUC0‐t ) for dutasteride and tamsulosin, and AUC0‐∞ for tamsulosin. The 90% confidence intervals for the ratios of the Cmax and AUC0‐t (for dutasteride and tamsulosin) and for AUC0‐∞ (for tamsulosin) were all completely contained within the range of 80% to 125%; therefore, the reformulated DTC capsule is bioequivalent to the commercial formulation under both fed and fasted states.